2012
DOI: 10.21608/jacb.2012.55014
|View full text |Cite
|
Sign up to set email alerts
|

SYMBIOTIC NITROGEN FIXATION OF FABA BEAN PLANTS INOCULATED WITH SALT-TOLERANT Rhizobium ISOLATES

Abstract: Rhizobium leguminosarum biovar viciae isolated from salt-affected faba bean fields were in vitro tested. Different isolates were found to be varied in their tolerance to salinity. F1 and E1 were found to be the most salt-tolerant isolates even at EC-level of 12 ds m-1. Seeds of Nubaria 1 cv. were inoculated with either F1 or E1, in comparison with a less salt-tolerant one (F9) in pots their salinity were adjusted at 0, 3, 6, 9 and 12 ds m-1 under aseptic conditions. Number and dry weight of nodules were decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…[27] reported that inoculation of the Rhizobium strain with faba bean seeds produced highest nodules. Likewise, the results of [26] and [28] confirmed that inoculation of Rhizobium strains in faba beans significantly increased the number of nodules. Desta et al [23] also reported that inoculation of rhizobia from faba bean significantly increases the number of nodules/plant.…”
Section: Effect Of Inoculation On the Number Of Nodulessupporting
confidence: 54%
“…[27] reported that inoculation of the Rhizobium strain with faba bean seeds produced highest nodules. Likewise, the results of [26] and [28] confirmed that inoculation of Rhizobium strains in faba beans significantly increased the number of nodules. Desta et al [23] also reported that inoculation of rhizobia from faba bean significantly increases the number of nodules/plant.…”
Section: Effect Of Inoculation On the Number Of Nodulessupporting
confidence: 54%